Federalism in Nigeria: Problems and Restructuring Option - Kelly Bryan Ovie Ejumudo; Francis Ayegbunam Ikenga (Unnes Law Journal, 2021)
The study examined the problematic of Nigeria’s federalism and the restructuring option. Three null hypotheses were formulated to guide the study and the study being a quantitative research adopted correlational design and four hundred academic staff from five Departments in the Faculty of social sciences all from the six sampled public Universities in the six geopolitical zones in Nigeria were sampled. The primary data that were used for the study were obtained from federalism and restructuring option questionnaire and chi square was used to analyze the data obtained. The finding of study revealed that the inability of the Nigerian state to adopt the restructuring option as a panacea to the unending political and ethnicity crises in the nation have a relationship with poor generating capacity and dependency mentality of the federating units. The study lucidly showed that there is no significant relationship between the nature and character of the age-long North-South tendencies and federalism in Nigeria. The study equally revealed that there is a significant relationship between politics of marginalization, socio-economic development and participatory/empowerment on federalism in Nigeria. The study recommended that to ensure peaceful coexistence of Nigeria’s multi-ethnic nationalities, the Nigerian government at different levels, different stakeholders and concerned bodies should go back to the drawing board and consider the creation of additional states and re-examine the sharing formula based largely on genuine need, derivation and population. The study also recommended that for the federalism option to succeed in Nigeria, there in need for re-construction, re-formulation, genuine acceptance and practicability of an appropriate federal arrangement that emphasizes self and national development as well as an equitable fiscal system that accommodates the true power relations and the expenditure and revenue realities of the respective component units in the Nigerian federation.